2021
DOI: 10.3389/fpsyg.2021.646145
|View full text |Cite
|
Sign up to set email alerts
|

What Type of Social Support Is Important for Student Resilience During COVID-19? A Latent Profile Analysis

Abstract: In the face of the sudden outbreak of coronavirus 2019 (COVID-19), some students showed resilience in coping with difficulties while some did not. While different types of students showed different levels of resilience, are there significant characteristics among students with similar levels of resilience? In this study, 3,454 students (aged 15–25 years) were surveyed to understand students' perceived social support-coping modes while investigating the demographic characteristics and mental health status of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
45
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 43 publications
5
45
0
4
Order By: Relevance
“…Resilience is the ability to rise from adversity [12]. In the educational context, studies have shown that resilience affects students' psychological well-being and positive behaviors during the COVID-19 pandemic [12][13][14][15]. Therefore, in this study, resilience, a variable studied in positive psychology, is set as a moderated mediation variable, as research shows that students with strong resilience tend to cope with stressful situations more actively.…”
Section: Introductionmentioning
confidence: 98%
“…Resilience is the ability to rise from adversity [12]. In the educational context, studies have shown that resilience affects students' psychological well-being and positive behaviors during the COVID-19 pandemic [12][13][14][15]. Therefore, in this study, resilience, a variable studied in positive psychology, is set as a moderated mediation variable, as research shows that students with strong resilience tend to cope with stressful situations more actively.…”
Section: Introductionmentioning
confidence: 98%
“…A Chinese study sampled on 7143 college-level medical students found a negative association between social support and anxiety (Cao et al, 2020 ). A cross-sectional study of 3454 vocational college students found that perceived social support was negatively correlated with general anxiety as well (Mai et al, 2021 ). Survey from 506 university students in Turkey also justified the negative relationship between social support and quarantine-related anxiety (Yalcin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Objective support was further categorized into family support and counselor support to highlight the situational nature of social support in COVID-19 pandemic. There is a need for the distinction of the sources of objective support in that Chinese students regarded support from family and friends as the most used support and support from teachers as the least used one (Mai et al, 2021 ). Family support referred to the availability of objective support from family and counselor support tapped the utilization of support from psychological counselors when individual met mental stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding SS, studies focused on person approach profiles have found that SS levels may vary between individuals. In this venue, different subgroups may be distinguished according to their degree of perception of support (Mai et al, 2021). However, Ciarrochi et al (2017) further considered the type of support perceived, such as family support, friends, and teachers.…”
Section: Introductionmentioning
confidence: 99%